PEMANFAATAN TEKNOLOGI GENOMIKA DAN TRANSFORMASI GENETIK UNTUK MENINGKATKAN PRODUKTIVITAS KELAPA SAWIT / The Use of Genomic and Genetic Transformation Technologies for Oil Palm Productivity Improvement - I Made Tasma (Puslitbang Perkebunan, 2016)
One of the main constrains oil palm cultivation in Indonesia is the low productivity with national yield average of 4 ton oil/ha/year much lower than the yield potential of up to 18.5 ton oil/ha/year. Conventional breeding method is a slow process and time consuming. It takes 10-12 years just to complete a breeding cycle. Applying genomic together with DNA tansformation methods should expedite oil palm breeding program. The objective of this manuscript was to review the application of genomic and DNA transformation technologies to improve oil palm productivity and its potential use for yield improvement program in Indonesia. Genomic technology has resulted reference genome sequence map of two oil palm species (E. guineensis and E. oleifera) that resulted the isolation of Sh gene controlling oil yield heterosis, discovery of mantled fruit mechanism, and as a foundation for superior gene and tait-associated marker discoveries to accelerate oil palm breeding program. The use of Sh gene markers together with mantled fruit detection kit at early stages of plant development accelerates oil palm breeding cycle and facilitates mantled seedling detection to guarantee productivity improvement. Multiplication of superior individual plants using in vitro culture should guaranty plantation high productivity in the field. Genetic engineering technique is potentially applied to improve palm oil quality and nutrition content as well as developing products useful for producing bioplastics. Resequencing studies of three Indonesian oil palm genotypes resulted millions of genomic variations (SNPs and Indels) important for high valued breeding resources to accelerate national oil palm breeding programs. Genomic as well as DNA transformation technologies are potentially applied in Indonesia to support national oil palm productivity and oil quality improvement programs.